2012
DOI: 10.1101/gr.132878.111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiles in hematopoietic stem and progenitor cells reveal overrepresentation of ETS transcription factor binding sites

Abstract: DNA methylation is an essential epigenetic mark that is required for normal development. Knockout of the DNA methyltransferase enzymes in the mouse hematopoietic compartment reveals that methylation is critical for hematopoietic differentiation. To better understand the role of DNA methylation in hematopoiesis, we characterized genome-wide DNA methylation in primary mouse hematopoietic stem cells (HSCs), common myeloid progenitors (CMPs), and erythroblasts (ERYs). Methyl binding domain protein 2 (MBD) enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 50 publications
(69 reference statements)
6
75
0
Order By: Relevance
“…These analyses have uncovered numerous types of chromatin regulators, including members of many transcription factor complexes and their downstream targets as well as regulators of the metabolome, protein synthesis, and mediators of signaling responses to external cues. [47][48][49][50][51][52] Indeed, the multiplicity of entities that appear to have nonredundant roles has been disconcerting in suggesting the lack of a singular pathway or state that regulates the maintenance of LTRC potential, or that distinguishes these cells from derivatives that appear irreversibly destined to differentiate in available assay systems. Rather, current findings suggest the involvement of highly complex and possibly alternative molecular networks controlling LTRC self-renewal that may require systems approaches to elucidate.…”
Section: Hsc Purificationmentioning
confidence: 99%
“…These analyses have uncovered numerous types of chromatin regulators, including members of many transcription factor complexes and their downstream targets as well as regulators of the metabolome, protein synthesis, and mediators of signaling responses to external cues. [47][48][49][50][51][52] Indeed, the multiplicity of entities that appear to have nonredundant roles has been disconcerting in suggesting the lack of a singular pathway or state that regulates the maintenance of LTRC potential, or that distinguishes these cells from derivatives that appear irreversibly destined to differentiate in available assay systems. Rather, current findings suggest the involvement of highly complex and possibly alternative molecular networks controlling LTRC self-renewal that may require systems approaches to elucidate.…”
Section: Hsc Purificationmentioning
confidence: 99%
“…50 The MBD domain MBD2 was recently used to affinity-purify methylated DNA fragments from mouse HSCs, CMPs, and erythroblasts to determine changes in 5mC during myeloid differentiation. Using this method, a high level of 5mC was detected in mouse HSCs, with a dramatic loss of global methylation occurring during myeloid differentiation, 51 similar BLOOD, 18 APRIL 2013 x VOLUME 121, NUMBER 16 …”
Section: Dna Methylation Readersmentioning
confidence: 94%
“…Detailed information on the localization, sequence characteristics of DNA targets, and associated binding partners is now available for ETS transcription factors in a range of cell types and developmental contexts. 27,[50][51][52][53][54][55] Although various levels of redundancy and specificity are observed that correlate with the ontology of the genes involved, one recurring feature is the close correspondence between in vivo and in vitro DNA sequence preferences. Moreover, in the case of PU.1 and Ets-1, the information contents (a direct informatic measure of target specificity) of the in vivo sequences preferences shown by both proteins are over 15% higher (> 3 bits over a 10-bp sequence space) than their in vitro counterparts.…”
Section: Combinatorial Routes To Ets Target Specificitymentioning
confidence: 99%
“…Genomic surveys have found that hematopoietic ETS transcription factors are over-represented in hypermethylated regions. 53 While several close class I ETS paralogs (such as Ets-1 and GABPa) have been reported to be inhibited by CpG methylation at their cognate sites, whether inhibition is a universal property of ETS proteins remains unknown. We have directly studied the binding properties of PU.1 and Ets-1 to hemi-methylated and fully methylated cognate DNA harboring a site-specific CpG dinucleotide (5 0 -CGGAA-3 0 ) that frequently occurs in cognate ETS binding sites.…”
Section: Differential Tolerance To Cpg Methylationmentioning
confidence: 99%
See 1 more Smart Citation